2016
DOI: 10.1002/bit.25974
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐color reporter switching system to discern dimer formations of G‐protein‐coupled receptors using Cre/loxP site‐specific recombination in yeast

Abstract: G-protein-coupled receptors (GPCRs) are physiologically important membrane proteins that represent major molecular targets in pharmaceutical and medicinal fields. Many GPCRs have been shown to form not only homodimers, but also heterodimers that can confer large functional and physiological diversity and are therefore expected to offer new opportunities for the discovery of new drugs. Yeast is a useful host organism that can be used to investigate the interactions between eukaryotic protein pairs, as demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Reporter gene expression was successfully switched in the engineered yeast cells and permitted the detection of the dimerized yeast endogenous pheromone receptor (Ste2p). The authors also validated the applicability of this system for monitoring the formation of human GPCRs homodimers and heterodimers, specifically human serotonin 1A receptor or β2-adrenergic receptor, and confirmed that this system had improved sensitivity when compared with the previous system [134]. Using a modified split-ubiquitin mY2H approach, Sokolina et al reported the systematic interactome analysis of 48 clinically important human GPCRs in their ligand-unoccupied state [135].…”
Section: Peripheral Membrane Proteinsmentioning
confidence: 75%
See 1 more Smart Citation
“…Reporter gene expression was successfully switched in the engineered yeast cells and permitted the detection of the dimerized yeast endogenous pheromone receptor (Ste2p). The authors also validated the applicability of this system for monitoring the formation of human GPCRs homodimers and heterodimers, specifically human serotonin 1A receptor or β2-adrenergic receptor, and confirmed that this system had improved sensitivity when compared with the previous system [134]. Using a modified split-ubiquitin mY2H approach, Sokolina et al reported the systematic interactome analysis of 48 clinically important human GPCRs in their ligand-unoccupied state [135].…”
Section: Peripheral Membrane Proteinsmentioning
confidence: 75%
“…Furthermore, the authors subsequently designed a reporter switching system that can switch the expressions between two reporter genes (one from ON to OFF and the other from OFF to ON) in response to the Y2H readout (Figure 2C and D) [134]. Cre/loxP site-specific recombination was employed to induce reporter switching.…”
Section: Peripheral Membrane Proteinsmentioning
confidence: 99%
“…The Cre recombinase and loxP sequence are both necessary for the initiation of the recombination reaction. Hence, this system can be applied in different ways such as fate mapping and gene regulation [ 23 , 24 , 25 , 26 ]. It was well known that Cre and loxP have a unique role in DNA recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Reporter gene expression was successfully switched in the engineered yeast cells and permitted the detection of the dimerized yeast endogenous pheromone receptor (Ste2p). The authors also validated the applicability of this system for monitoring the formation of human GPCRs homodimers and heterodimers, specifically human serotonin 1A receptor or β2-adrenergic receptor, and confirmed that this system had improved sensitivity when compared with the previous system [134].…”
Section: Membrane Y2h Technology To Study Gpcr Oligomers In Yeast Cellsmentioning
confidence: 66%